William Shakespeare's Hamlet - Bloom, Harold (New Delhi : Viva Books, 2008)
Hamlet is commanded by his father to avenge his murder at the hands of his own brother, Hamlet's uncle Claudius, who has since become king and married Hamlet's mother, Gertrude.
Includes index.
Keywords: Hamlet